Welfare impacts of improved groundnut varieties adoption and food security implications in the semi-arid areas of West Africa - Lokossou, Jourdain C.; Affognon, Hippolyte D.; Singbo, Alphonse; Vabi, Michel B.; Ogunbayo, Ayoni; Tanzubil, Paul; Segnon, Alcade C.; Muricho, Geoffrey; Desmae, Haile; Ajeigbe, Hakeem A. (Springer, 2022)
This paper investigates the welfare impacts of improved groundnut adoption in Ghana, Mali, and Nigeria using three-year balanced panel data collected from 2,868 households. We apply the Cragg double hurdle model to understand the adoption process and a fixed-effects instrumental variable approach to estimate the impact on gross margins, household income, per capita income, food security, and poverty. The results show that a 10% increase in the area planted with improved groundnut varieties is associated with a 25.6%, 14.8%, 6.9%, and 23.6% increase in groundnut gross margins, household income, per capita income, and food consumption score, respectively. Likewise, this leads to a 3.6% poverty reduction. The highest average impact is found in Nigeria, followed by Ghana and Mali. Furthermore, disaggregating the impacts by adoption history reveals that households that continuously adopted the improved groundnut varieties benefited more than other categories of adopters. They enjoy a 6.6% poverty reduction compared to 1.9% for households that cultivated improved groundnut varieties for a single year. We conclude that improved groundnut varieties' adoption is a promising pathway for rural poverty alleviation and food security improvement. Hence, encouraging households to adopt improved groundnut varieties for consecutive years could help capitalize on income gains and contribute to raising households above the poverty threshold.